SOSIALISASI PEMANFAATAN MS.OFFICE, INTERNET, DAN PENGGUNAAN MENDELEY UNTUK MERANCANG PENELITIAN BAGI MAHASISWA STT DUTA BANGSA CIKARANG-BEKASI - Cahyadi Husadha; Wastam Wahyu Hidayat; Adelina Suryati; Ery Teguh Prasetyo; Istianingsih; Kardinah Indrianna Meutia (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
This Community Service activity aims to provide education, knowledge, understanding, action, and skills from an early age in the use of information and communication technology in the context of designing research by combining the use of MS applications. Office, internet, and the use of the Mendeley program application for undergraduate students (S1) STT Duta Bangsa-Cikarang. The method used in the implementation of this PKM activity is concept mapping (network of information on students' initial knowledge), basic reasoning, recognizing and explaining the advantages of technology and information, and procedures for using the Mendeley program application accompanied by the provision of direct practice in running the program. application of the program. This training involved lecturers and students of the Faculty of Economics and Business, Bhayangkara University, Greater Jakarta as the executor of this PKM activity, and STT Duta BangsaCikarang students as participants. And finally, our hope is to get an understanding that goes along with a common thought. That the application of programs and the use of information technology can assist in the process of facilitating and smoothing the completion of student assignments in preparing research/thesis, and making it easier for lecturers to check in technical research/thesis.Keywords : Socialization of Application Utilization, Microsoft Office, Internet, Mendeley, and Designing Research.